Desarrollo De Una Solución Software Para El Apoyo De La Asistencia Psicosocial (2019)
Admission to the university is the beginning of a new stage in a person's life, entering at a very young age or not being prepared for this change can bring negative consequences. One of these is desertion, which has been analyzed different causes and one of the reasons are the external processes associated with education, as is the socioeconomic context. Many new students have the benefit of a scholarship; however, these mostly do not cover the multiple expenses that the university causes and it does not fix the economic conditions in the student's home, this type of pressure can cause not only emotional damage but also physical damage. The purpose of this project is to design and implement a software solution to support the psycho-social intervention programs of the University Welfare Office through the development of a multiplatform application. The methodology proposed for the management of the project is the agile SCRUM methodology, mainly because it is a much more flexible type of practice, given that this type of methodologies are really useful for projects where the requirements are not fully defined. The solution consists of 5 modules which were made in the following sprints: login and registration, virtual assistant (communication channel), forum (help group), educational agenda + emergency button and promotional or informative space. The implementation of an alternative channel for University Welfare will allow students to have a first approach to psychotherapy by facilitating the student community to use the means provided by Universidad del Norte in a more practical environment. In turn, our system would guarantee users a secure and private environment, given that many areas of interaction will handle anonymous users, however, the security system will collect data, records and interaction using their real names.